Massachusetts Substance Use Disorder Treatment Organizations' Perspectives on the Affordable Care Act: Changes in Payment, Services, and System Design. Issue 2 (15th March 2017) - Quinn, Amity E.; Stewart, Maureen T.; Brolin, Mary; Horgan, Constance M.; Lane, Nancy E.
ABSTRACT: The Affordable Care Act (ACA) expanded insurance benefits and coverage for substance use disorder (SUD) treatment and encouraged delivery and payment reforms. Massachusetts passed a similar reform in 2006. This study aims to assess Massachusetts SUD treatment organizations' responses to the ACA. Organizational interviews addressing challenges of and responses to the ACA were conducted in person June–December 2014 with 31 leaders at 12 treatment organizations across Massachusetts. Many organizations were affiliated with medical or social services and offered a range of SUD services. Sampling was based on services offered (detoxification only, detoxification and outpatient, outpatient only). Framework analysis was used. Challenges identified were considered similar to ongoing challenges, not unique to the ACA. Organizations experienced insurance expansions in 2006 and faced new challenges, including insurance coverage, payment arrangements, expansion of services, and system design. System design efforts included care coordination/integration, workforce development, and health information technology. Differences in responses related to connections with medical and social service organizations. Many organizations engaged in efforts to respond to changing policies by expanding capacity and services. Offering a range of SUD treatment (e.g., detoxification and outpatient) and affiliating with a medical organization could enable organizations to respond to new insurance, delivery, and payment reforms.